2016
DOI: 10.1186/s12944-016-0337-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased ANGPTL3, 4 and ANGPTL8/betatrophin expression levels in obesity and T2D

Abstract: BackgroundHypertriglyceridemia is associated with increased risk for cardiovascular diseases and type 2 diabetes (T2D). Angiopoietin like proteins particularly 3, 4 and recently 8 are well established regulators of plasma triglyceride level through regulating the activity of lipoprotein lipase. Plasma level and association between ANGPTL3, 4 and 8 is not well established in human subjects. This study was designed to establish the level of these proteins in plasma and adipose tissues and investigate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
78
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 36 publications
13
78
2
1
Order By: Relevance
“…Our data show that the increase in ANGPTL‐4 levels in obesity is higher in those individuals with ATG, and that there is a positive correlation between ANGPTL‐4 and HOMA‐IR and HbA1C. Similarly, two recent articles showed that plasma levels of ANGPTL‐4 are increased in T2D subjects with respect to nondiabetic individuals . In concordance with these findings in humans, ANGPTL‐4 transgenic mice showed a worsening of glucose metabolism when fed a high‐fat diet .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data show that the increase in ANGPTL‐4 levels in obesity is higher in those individuals with ATG, and that there is a positive correlation between ANGPTL‐4 and HOMA‐IR and HbA1C. Similarly, two recent articles showed that plasma levels of ANGPTL‐4 are increased in T2D subjects with respect to nondiabetic individuals . In concordance with these findings in humans, ANGPTL‐4 transgenic mice showed a worsening of glucose metabolism when fed a high‐fat diet .…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, two recent articles showed that plasma levels of ANGPTL-4 are increased in T2D subjects with respect to nondiabetic individuals. [22,32] In concordance with these findings in humans, ANGPTL-4 transgenic mice showed a worsening of glucose metabolism when fed a high-fat diet. [3] Altogether, it seems that elevated levels of ANGPTL-4 are related to a poor glucose tolerance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…13 Our current findings showed that ANGPTL3 expression was upregulated under high glucose stimulation in HRMECs and in the retinas of diabetic rats. To investigate the relationship between ANGPTL3 and diabetic retinopathy, we measured the protein and RNA expression levels of genes involved in inflammation and apoptosis in both HRMECs and rat retinas before and after ANGPTL3 siRNA intervention under high glucose conditions.…”
Section: Discussionsupporting
confidence: 49%
“…Most of the recent studies suggest that plasma ANGPTL8 levels are elevated in type 2 diabetes (T2D), insulin resistance or obesity (Abu-Farha et al, 2016;Chen et al, 2015;Fu et al, 2014). However, ANGPTL8 was found to be the the most strongly insulin-induced individual gene in human WAT in vivo (Nidhina Haridas et al, 2015;Soronen et al, 2012), suggesting that, apart from its function in the circulation, it may also execute an unknown intracellular function in adipocytes.…”
Section: Introductionmentioning
confidence: 99%